2015
DOI: 10.5897/ajb2014.14179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute toxicity profile of Lasianthera africana leaf extract in normal rats and its ameliorative effect in alloxan-induced diabetic rats

Abstract: The present study evaluated the acute toxicity effect of Lasianthera africana leaf extract on normal rats and effect of the extract on the hepatic and renal function indices in alloxan-induced diabetic rats. In the acute toxicity test, male Wister rats received orally four different single dose of the extract and were kept under observation for 14 days. The result indicates that LD 50 of the extract is higher than 5,000 mg/kg body weight. For the second experiment, doses (50, 100 and 200 mg/kg body weight) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The reduction in leukocyte counts when treating diabetic rats with both commercial and laboratory-produced acarbose may be due to the anti-inflammatory, antioxidant, and free radical scavenging activities of it. This agrees with Baba et al (2018. The other effects of chronic hyperglycemia mentioned above may have been counteracted by the hypoglycemic effect of the leaves (Inyang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The reduction in leukocyte counts when treating diabetic rats with both commercial and laboratory-produced acarbose may be due to the anti-inflammatory, antioxidant, and free radical scavenging activities of it. This agrees with Baba et al (2018. The other effects of chronic hyperglycemia mentioned above may have been counteracted by the hypoglycemic effect of the leaves (Inyang et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…al., 2018. The other effects of chronic hyperglycemia mentioned above may have been counteracted by the hypoglycemic effect of the leaves (Inyang, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in WBC count upon treatment of diabetic rats with the mushroom extracts may be attributable to its ant-inflammatory action (Okokon et al, 2013), antioxidant effect (Atiko et al,2016 and free radical scavenging activity ( Baba et al, 2018). The other effects of chronic hyperglycemia mentioned above may have been countered by the hypoglycemic effect of the mushroom (Inyang et al,2015). The results from this study therefore reveals that extracts from Pleurotusostreatus samples may be used to improve immune function against infection.…”
Section: Hematologicalmentioning
confidence: 69%
“…Since hyperglycemia is behind the activation (Papatheodorou et al, 2018), the mushroom extract may have produced the observed effects through reduction in blood glucose since it has hypoglycemic activity (Inyang et al, 2015).…”
Section: Hematologicalmentioning
confidence: 99%